2013
DOI: 10.7600/jspfsm.62.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volunteerism as exercise instructor on physical and cognitive function in community-dwelling elderly women

Abstract: The purpose of this study was to examine whether volunteering as exercise instructors over a continuous period of time affected the physical and cognitive functions of community-dwelling, elderly women. Longitudinal analysis was conducted on data from 18 volunteer leaders (Leader group) aged 65-79 years (69.6 ± 3.9 years) and 18 age-matched survey participants (Control group). We evaluated physical function using 8 physical performance tests along with their standardized total score, and we evaluated cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As for the relationship between volunteering and physical activity, Mitsuishi et al reported that the amount of physical activity increased with volunteering [ 23 ] and suggested that it is necessary to investigate the type and frequency of volunteer activity in order to better understand this association. In addition, older adults with hypertension are characterized as having a “nondipper” type of nocturnal blood pressure (BP) in which nocturnal BP fluctuations inhibit the usual decrease in BP during the nighttime [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the relationship between volunteering and physical activity, Mitsuishi et al reported that the amount of physical activity increased with volunteering [ 23 ] and suggested that it is necessary to investigate the type and frequency of volunteer activity in order to better understand this association. In addition, older adults with hypertension are characterized as having a “nondipper” type of nocturnal blood pressure (BP) in which nocturnal BP fluctuations inhibit the usual decrease in BP during the nighttime [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the sample size of this cohort study is smaller than other relevant cohort studies, this study has the advantage of assessing various physical performance tests including reaction time 9) , postural sway 10,15) , ground reaction force in sit-to-stand movement 7,13) , and cognitive function 11) . The information obtained has been used as control data for all-round exercise classes and voluntary group exercise activities 27) in addition to regular cross-sectional and longitudinal studies.…”
Section: Annual Follow-up Study On the Kasama Health Checkup For Longmentioning
confidence: 99%
“…We have held SSE elderly leadership training seminars since September 2009 to train elderly volunteers, called SSE leaders, who manage voluntary group exercise activities; they provide technical and emotional support for community-dwelling elderly to engage in SSE 27) . One course is comprised of weekly training seminars over a period of 5 weeks.…”
Section: Summary Of Voluntary Group Exercise Activities and Training mentioning
confidence: 99%
“…The exercise technique includes forward, backward, lateral, and oblique steps, with a progressive increase in the step pattern complexity. SSE has been applied as the main exercise in voluntary exercise salons for healthy elderly individuals (Mitsuishi et al, 2013), exercise programs that are aimed at preventing care needs for older adults (Jindo et al, 2015), and rehabilitation programs for post-stroke patients (Túbero et al, 2014). The SSE program consisted of a warm-up activity (15 min), SSE (40 min), a recreational activity (20 min), and a cool-down period (15 min).…”
Section: Exercise Programmentioning
confidence: 99%